2017
DOI: 10.3389/fimmu.2017.00124
|View full text |Cite
|
Sign up to set email alerts
|

Stretching Reduces Skin Thickness and Improves Subcutaneous Tissue Mobility in a Murine Model of Systemic Sclerosis

Abstract: ObjectiveAlthough physical therapy can help preserve mobility in patients with systemic sclerosis (SSc), stretching has not been used systematically as a treatment to prevent or reverse the disease process. We previously showed in rodent models that stretching promotes the resolution of connective tissue inflammation and reduces new collagen formation after injury. Here, we tested the hypothesis that stretching would impact scleroderma development using a mouse sclerodermatous graft-versus-host disease (sclGvH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…In order to investigate how stretching might affect breast cancer tumor growth, we adapted a well-established protocol for gentle stretching in mice 24 , 25 in which mice are held by the tail and gently lifted, allowing the front paws to grasp a bar (Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate how stretching might affect breast cancer tumor growth, we adapted a well-established protocol for gentle stretching in mice 24 , 25 in which mice are held by the tail and gently lifted, allowing the front paws to grasp a bar (Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, five studies used devices either on top of the skin or subcutaneously to deliver a static stretching protocol [ 25 28 , 40 ]. Four studies performed an active stretching intervention by lifting rats and mice by the tail until reaching an approximately 45° angle and increasing the distance between the shoulders and hips by ~25% [ 8 , 41 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent cross-sectional study of 537 patients with scleroderma in five European countries, 80–92% reported joint pain, and nearly as many (70–86%) reported “muscle” pain [ 49 ]. Although it is not clear what role, if any, fascia adhesions may play in these symptoms, a murine model of GVHD demonstrated reduced shear plane motion between fascia layers, similar phenotypically to the reduced fascia mobility observed in patients with chronic low-back pain [ 50 ].…”
Section: Does Generalized Hypo- or Hypermobility Predispose One To Or Protect From Myofascial Pain?mentioning
confidence: 99%